2012
DOI: 10.1142/s0217732312300030
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Naturalness and Dark Matter Prediction for the Higgs Mass in MSSM and Beyond

Abstract: Within a two-loop leading-log approximation, we review the prediction for the lightest Higgs mass (m h ) in the framework of constrained MSSM (CMSSM), derived from the naturalness requirement of minimal fine-tuning (∆) of the electroweak scale, and dark matter consistency. As a result, the Higgs mass is predicted to be just above the LEP2 bound, m h = 115.9 ± 2 GeV, corresponding to a minimal ∆ = 17.8, value obtained from consistency with electroweak and WMAP (3σ) constraints, but without the LEP2 bound. Due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…(A.2), there are also contributions from other operators and it have been discussed, for example, in refs. [64][65][66][67][68][69]. 13 Open Access.…”
Section: Jhep07(2014)134mentioning
confidence: 99%
“…(A.2), there are also contributions from other operators and it have been discussed, for example, in refs. [64][65][66][67][68][69]. 13 Open Access.…”
Section: Jhep07(2014)134mentioning
confidence: 99%
“…Moreover, imposing universal boundary conditions, which is what characterises the cE 6 SSM, means that all low energy SUSY parameters can be expanded in terms of a few GUT-scale universal and fundamental input parameters, namely,…”
Section: The Higgs Potential and The Ewsb Conditionsmentioning
confidence: 99%
“…The large radiative contributions from stops needed to raise it to the observed value typically imply very large fine tuning. For example the constrained MSSM (cMSSM) [5] has been shown to require fine tuning of O(1000) if it is to contain a 125 GeV Higgs mass [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For M of the order of a few TeV, the non-renormalizable corrections of the BMSSM are sizeable and they have been analyzed in the context of electroweak baryogenesis [15][16][17], dark matter [16,[18][19][20][21][22][23][24], Higgs phenomenology [25][26][27] and collider phenomenology [28,29]. In a nutshell, it has been shown that the consequence of this simple extension of the MSSM including higher order operators which are suppressed by inverse powers of a scale of new physics somewhat higher than the electroweak breaking scale, can significantly relax the constraints coming from the above mentioned physical observables.…”
Section: Jhep07(2011)074mentioning
confidence: 99%